Rapid Femoral Vein Assessment (RaFeVA): A systematic protocol for ultrasound evaluation of the veins of the lower limb, so to optimize the insertion of femorally inserted central catheters. Issue 6 (November 2021) - Brescia, Fabrizio; Pittiruti, Mauro; Ostroff, Matthew; Biasucci, Daniele G
In this paper we describe a new protocol—named RaFeVA (Rapid Femoral Vein Assessment)—for the systematic US assessment of the veins in the inguinal area and at mid-thigh, designed to evaluate patency and caliber of the common and superficial femoral veins and choose the best venipuncture site before insertion of a FICC.